Upgrading bandwidth of rectangular patch antenna using metamaterial / Ahmad Syazwan Nasaruddin - Nasaruddin, Ahmad Syazwan (2008)
This paper is proposed a metamaterial in constructing a patch antenna. It is done by implementing a metamaterial as substrate of the antenna. The study is concentrating on X-band frequency at 11.28 GHz. This design can reduce the size of the antenna as well as maintaining the return loss response and able to increase the bandwidth. The newly invented metamaterial antenna maintained return loss of less than -20dB and 300MHz wider bandwidth if compared to the conventional antenna. The size of the metamaterial antenna is reduced by a factor of 2. The metamaterial is obtained by combining two materials which are the Flame Retardant 4 (FR-4) and the Copper in the structure of Symmetrical- Ring. The S-paramcter obtained from simulation of the metamaterial is ensured to be negative in order for it to be a metamaterial. This metamaterial antenna is surely good news for communication industries as antenna can now be produced at smaller size but still can response similarly or even better than the conventional antenna nowadays. This metamaterial antenna has positive future in helping the telecommunication industries to move one step further in enhancing their technology thus giving satisfaction to the customers.